Creative writing in health and social care - Sampson, Fiona (Jessica Kingsley Publishers, 2004)
This unique and comprehensive 'map' of the topic of creative writing in health and social care brings together contributions from health and social care professionals and provides the information needed to teach, counsel and write. Principally exploring poetry and story writing and telling, case studies range from work with pre-literate children in post-war Macedonia to people with dementia in Britain. Complementing these insights, theory-based contributions provide context, comparing different arts therapies using psychoanalytic and phenomenological theories of art and ideas, assessing the va.